The humanities culture, continuity & change - Sayre, Henry M., 1948- (Pearson Prentice Hall, 2008)
v. I Prehistory to 1600 -- bk. 1. The ancient world and the classical past : prehistory to 200 CE -- bk. 2. Medieval Europe and the shaping of world cultures : 200 CE to 1400 -- bk. 3. The Renaissance and the age of encounter : 1400 to 1600 --v. II 1600 to the present -- bk. 4. Excess, inquiry, and restraint : 1600 to 1800 -- bk. 5. Romanticism, realism, and empire : 1800 to 1900 -- bk. 6. Modernism and the globalization of cultures : 1900 to the present.